The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1080/10810730.2011.626505
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Emotional Health Risk Perceptions Among People Living in Poverty

Abstract: Many theories of risk perception and health behavior examine cognitive dimensions of risk (i.e., perceived susceptibility or severity) but not emotional dimensions. To address this gap, the authors examined the emotional component of risk perception (as worry) and its relation to cognitive assessments of risk, self-efficacy and response efficacy, and health protective action. Although people in poverty are at high risk for many health conditions, little is known about how concerned they are about these conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
0
12
0
1
Order By: Relevance
“…To measure the self-efficacy, the attitude, and the preventative behavior of amateur marathon runners on preventative behavior, the scale developed by Freimuth 46 and revised by Huang 28 was adopted. Self-efficacy was measured with the item, “Before running a marathon, how confident are you that you can take precautions to reduce [insert risk]?…”
Section: Methodsmentioning
confidence: 99%
“…To measure the self-efficacy, the attitude, and the preventative behavior of amateur marathon runners on preventative behavior, the scale developed by Freimuth 46 and revised by Huang 28 was adopted. Self-efficacy was measured with the item, “Before running a marathon, how confident are you that you can take precautions to reduce [insert risk]?…”
Section: Methodsmentioning
confidence: 99%
“…Susceptibility reflects one's perception of the likelihood of contracting a disease, whereas severity refers to one's perception of the seriousness or harmfulness of a disease (El-Toukhy, 2015;Rimal & Real, 2003). In particular, when people perceive health-related risks, they not only rely on the cognitive aspects of the likelihood and severity of a healthrelated disease, but also use affective aspects of the worry, concern, or dread that a person feels about a health-related disease (e.g., Freimuth & Hovick, 2012;Oh, Paek, & Hove, 2015).…”
Section: Risk Perceptionmentioning
confidence: 99%
“…Freimuth and Hovick found that worry did not increase health protective action for the high-worry and high-action risk and positively increased health protective action for the high-worry but low-action risk. 68 We found that anxiety, anger, and dissatisfaction showed a significantly positive effect on WTP. In addition, people who strongly feared the risk posed by PM 2.5 were more willing to pay, which did not agree with Yang's finding that people who strongly feared the risk of greenhouse gasses showed lower WTP.…”
Section: Determinants Of Respondent's Wtpmentioning
confidence: 64%